Inducible immortalized Dendritic Cells enable antigen-specific antibody production in a murine in vitro Immunization model - Juliane Egert; Natalia Maier; Burkhard Micheel; Katja Hanack (PLoS ONE, 2026)
Transferring the complexity of the in vivo immune response into a controlled in vitro system represents a promising strategy for the rapid generation of antigen-specific antibodies while significantly reducing the reliance on animal experimentation, thus adhering to the 3Rs principle. In this study, we present an in vitro immunization (IVI) approach that employs conditionally immortalized dendritic cells (DCs), derived from a transgenic irtTA-GBD/T-Ag mouse model, to initiate antigen-specific immune responses in vitro . These dendritic cells can be kept in a proliferative state under tetracycline-controlled expression of the SV40 large T antigen (termed iniDCs) and maintained long-term in culture. Upon de-induction of the immortalizing transgene, the resulting deinduced iniDCs (de-iniDCs) regain physiological properties and exhibit full functional maturation in response to appropriate stimuli. When co-cultured with naïve murine T and B lymphocytes, these mature de-iniDCs are capable of initiating antigen-specific adaptive immune responses, culminating in the production of antigen-specific antibodies by B cells. By utilizing this standardized population of antigen-presenting cells, we have established a robust and reproducible IVI protocol that enables the generation of antigen-specific antibody responses in vitro . Antibody-secreting B cells were subsequently fused with myeloma cells, and antigen-specific hybridomas were rapidly identified and isolated using the novel selma ( selection of monoclonal antibody ) technology, allowing for an accelerated and efficient selection of antigen-specific monoclonal antibodies.